Implementation of Artificial Intelligence in Digital Marketing Development: a Thematic Review and Practical Exploration - Aditya Nirwana; Sudarmiatin; Melany (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to synthesize a comprehensive view of the use of AI in each stage of a series of marketing campaigns, including the stages of planning, initiating the marketing concept, marketing design, implementation and monitoring, and evaluation. By using the Systematic Literature Review (SLR) method, this study will try to